Mast cell mediated myofibroblast differentiation responsible for progression of oral submucous fibrosis - Mamatha GS Reddy; Pradnya Kakodkar; Vini Mehta (Oral Oncology Reports)
Myofibroblast from ally to adversary confirmed the role of myofibroblast in the progression of OSF. Several theories have been postulated regarding the etiopathogenesis of OSF, fibroblast being the key cell in causing fibrosis mediated by TGF. However, some fibroblasts have found to express features of smooth muscle differentiation which are referred to as myofibroblasts. In OSMF, both mast cells and myofibroblasts are shown to increase. We wish to propose a hypothesis that mast cells demonstrated in OSF through its granular contents histamine and tryptase may contribute in differentiating fibroblasts to myofibroblasts which are responsible for the fibrosis occurrence in OSF.